Anthropometric-based predictive equations developed with multi-component models for estimating body composition in athletes - Serafini, S.; Charrier, D.; Izzicupo, P.; Esparza-Ros, F.; Vaquero-Cristóbal, R.; Petri, C.; Mecherques-Carini, M.; Baglietto, N.; Holway, F.; Tinsley, G.; Paoli, A.; Campa, F. (European Journal of Applied Physiology, 2024)
Purpose Body composition can be estimated using anthropometric-based regression models, which are population-specific and should not be used interchangeably. However, the widespread availability of predictive equations in the literature makes selecting the most valid equations challenging. This systematic review compiles anthropometric-based predictive equations for estimating body mass components, focusing on those developed specifically for athletes using multicomponent models (i.e. separation of body mass into = 3 components).